EUSEBIUS ON CONSTANTINE AND NICAEA: INTENTIONS AND OMISSIONS - Marco Rizzi (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2013)
This article is dedicated to illuminating problems associated with one of the main sources of the history of the early church up to the time of the First Ecumenical Council — The Church History and the Life of the Emperor Constantine — both written by Eusebius of Pamphilus. The author points to the fact that these works have little to say about the theological disputes which were part and parcel of the First Ecumenical Council. Eusebius, instead, fills his account with details of the disputes concerning the date of the celebration of Easter. The arian controversies which dominate the pages of the works of other early Church Fathers are passed over in silence by Eusebius. Researchers have concluded that this was precisely the intention of Eusebius since he himself belonged to the party which sympathized with the heretic Arius. The author of this article attempts to refute this argument and offers another explanation. The author points out that Eusebius always devotes special attention to events and functions organized by Constantine. These events and activities are described by Eusebius in a way which deliberately excludes theological controversies. The author concludes that Eusebius, like Constantine himself, 28 М. Рицци. Евсевий о Константине и Никейском соборе: намерения и умолчания deliberately avoids mentioning the theological disputes since both considered them of relatively little importance and that their solution should be reserved to the narrow circle of intellectuals among the early churchmen. Eusebius thought that the conservation of ecclesiastical peace and unity was of primary importance for all his fellow bishops